KEGIATAN KOMUNIKASI PEMASARAN PRODUK DAN JASA â€œLARISSA SKIN CAREâ€ di SURAKARTA - Nurnawati Hindra H, Samirah Handayani, Bedjo Sukarno & (Transformasi, 2016)
This study aims to determine the marketing communication activities conducted by larissa skincare in promoting its products and services in the city of Surakarta. In obtaining the data usinginterviews, observation, documentation, and literature as a complete theory and concepts usedin the study. Method interviews conducted supported by purposive sampling technique, whichthe authors define a resource that consists of General Manager, Marketing Manager, StaffMarketing and Consumers or users of products and services Larissa Skin Care. The resultsshowed that Larissa Skin Care Surakarta implement. In the implementation of the campaigncarried Larissa Skin Care, applying the promotion mix (promotional mix) in the implementationof marketing communications. Among them are the activities of advertising, personal selling,sales promotion, public relations / publicity, word of mouth. Among the activities undertaken,advertising activities are preferred, especially in the use of online media, because the media isconsidered to be more effective and provide a pretty good response and fast enough in anypromotional program created by Larissa Skin Care.Keywords : Marketing Communications . Promotion Larissa Skin Care